Effects of lactic acid bacterial and chemical additives on the quality and biogenic amine production of oat silage at low temperature - Yuhan Huang; Tingting Jia (Frontiers in Sustainable Food Systems)
ObjectiveThe effects of low-temperature-resistant lactic acid bacteria (LAB) and chemical additives on the quality and biogenic amine production of oat (Avena sativa L.) silage stored at low temperature were investigated.MethodsThe Lactobacillus plantarum strain Y28, isolated from oat silage, demonstrated robust growth at low temperature. Fresh and wilted oat forages were treated with no additives (Con), L. plantarum inoculant (Y28), propionic acid (PA), formic acid (FA) and sodium benzoate (SB). Silages were opened after 30 or 60 days of storage, and their quality and biogenic amine production were evaluated.ResultsAfter fermentation, putrescine, cadaverine and tyramine were present at the highest levels in oat silage stored at low temperature, constituting approximately about 90% of the total biogenic amines measured. Five other amines, tryptamine, phenethylamine, histamine, spermidine and spermine were mostly detected at concentrations below 30 mg/kg. The concentrations of tryptamine, phenethylamine, putrescine, cadaverine, histamine, tyramine, spermidine and total biogenic amines, but not spermine, were higher in fresh oat silages compared to wilted oat silages after 30 or 60 days of fermentation. The Y28 inoculant improved the fermentation quality of oat silage at low temperature by lowering the pH and ammonia nitrogen content while increasing lactate content. Oat silage treated with Y28, PA, FA and SB showed lower concentrations of putrescine, cadaverine, tyramine and total biogenic amines than the control in both fresh and wilted oat silage after 30 or 60 days of fermentation.ConclusionAmong these treatments, FA was the most effective at suppressing the formation of tyramine, cadaverine and putrescine in oat silage stored at low temperature.